Investigation of complex urban lifeline systems - Khoo, Ruo Ting (2019)
This thesis is an investigation on complex urban lifeline systems, specifically water distribution systems (WDSs) and their resilience against multiple risks and threats. Global threats, natural or man-made, have been on the rise. Existing WDSs that are not designed to endure the increase in amount and scale of threats suffer from failures and breakdowns that have serious consequences on human daily life. There is a need to improve on existing systems and develop new systems with better designs in terms of their resilience towards failure. These improvements will make systems less vulnerable to threats and hence become more sustainable. A global resilience analysis (GRA) tool was used to analyse the performances of three different water networks in four various crises; pipe failure, pump failure excess demand and substance intrusion. For each failure cases, the range of each failure consequences and severe scenarios are identified by the GRA tool. The tool revealed that resilience for one failure mode could impact resilience for another, or even impact the overall recovery of the system. Stress-strain tests are used to analyse resilience and evaluate system performance based on various attributes, which could eventually aid in better network resilience designs. Upon testing three different WDSs under four different failure modes using the GRA tool, results show that the size of a WDS may not be the determining factor to its resilience. Furthermore, water networks that are less resilient in some failure modes could be more resilient in other modes. The GRA tool is effective in revealing the weakness of WDSs when subjected to various failure modes, which is useful when planning for future WDSs or when improving the resilience of existing WDSs.